IMPROVING UNIVERSITY STUDENTS’ READING COMPREHENSION USING GRAPHIC ORGANIZERS - Juella Rumiris (Fakultas Keguruan dan Ilmu Pendidikan Universitas Kristen Indonesia, 2014)
This study was a classroom action research aimed to improve EFL tertiary students’ reading comprehension by using graphic organizer, one of teaching methods used universally to help learners to understand reading deeper, especially for retelling story outcome.The participants were 44 undergraduate students attending the researcher Reading II class. The improvement in this study was focused on the participants’ skills of determining main idea, identifying topic, summarizing, and enriching vocabulary. To check students’ comprehension, the researcher measured the students’ reading comprehension using open-ended questions in written form, interview, as well as rubrics which are presented in both quantitative and qualitative data. The results revealed that there was no significant improvement in the participants’ main idea identification and vocabulary enrichment skills. However, there was robustly significant improvement in their topic identification and summarizing skills.Keywords : graphic organizer, reading comprehension, main idea, topic, summarizing